A new species of Agave (Asparagaceae) from Colombia and a taxonomic key for the South American species - Diego Alonso Giraldo Cañas (Caldasia)
As result of recent studies of South American Asparagaceae, one new species of Agave is described and illustrated. The morphological species concept was followed and SEM photographs of different vegetative and reproductive structures were taken. The new species inhabits a narrow endemic area of dry tropical forest of the Río Cauca Canyon (Antioquia, Colombia) and it belongs to subgenus Agave, group Sisalanae. It is morphologically related to Agave sisalana from Mexico, but clearly differs from it in various vegetative and reproductive characteristics, which are discussed. Based on IUCN criteria, the new species is categorized as endangered (EN). Thus, a total of six species of Agave are currently known in South America −five are native and one is naturalized−. A key to the South American species of Agave is presented.